Exploring the value of rectal anal canal pressure measurement in the diagnosis of Hirschsprung's disease. Issue 6 (June 2022) - Liang, Yuanyuan; An, Ting; Xin, Wenqiong
Abstract: Background: The value of rectal anorectal manometry (ARM) in the diagnosis of Hirschsprung's disease (HD), especially in newborns, has been controversial. This study aims to further explore the value of ARM in the diagnosis of HD. Methods: This study prospectively collected the rectal and anal canal pressure records of children with high suspicion of HD diagnosed by rectal suction biopsy (RSB) from the West China Hospital of Sichuan University from November 2019 to September 2021. With RSB results as the diagnostic gold standard, the value of ARM examination in the diagnosis of HD was explored through age stratification. Results: Among 170 children, the sensitivity of ARM in diagnosing HD was 98%, the specificity was 65%, and the accuracy was 93%. The positive likelihood ratio was 2.83, and the negative likelihood ratio was 0.03. The positive result of ARM is more important to HD. The positive predictive value was 94%, the negative predictive value of the ARM negative result for HD was 85%, the kappa value was 0.680, and the Yuedeng index was 0.63. Through age stratification, it was found that the sensitivity of ARM for HD diagnosis in each age group was relatively close, but the neonatal specificity was only 33%, which was significantly lower than that of children of other age groups. Conclusion: ARM has high sensitivity in HD children of all ages. In neonates, ARM has a high false positive rate in the diagnosis of HD. Highlights: This prospective study was performed to explore the value of anorectal manometry (ARM) in the diagnosis of Hirschsprung's disease (HD) through age stratification. Although there have been similar studies, most of the studies included children who had not undergone rectal suction biopsy (RSB) examination due to the small sample size in the diagnosis of HD. In our study, the children we included all had ARM and RSB test results, and the RSB results had not been known before ARM. The research method of comparing the difference between the two examination results of the same individual has a higher degree of credibility. The results revealed that ARM has high sensitivity in HD children of all ages. However, in neonates, ARM has a high false positive rate in the diagnosis of HD. Abstract : Rectal anal canal manometry, Hirschsprung's disease, Diagnosis.